Oropharyngeal cancer prognosis by tumour HPV status in France: The multicentric Papillophar study. (April 2017) - Lacau St Guily, Jean; Rousseau, Alexandra; Baujat, Bertrand; Périé, Sophie; Schultz, Philippe; Barry, Béatrix; Dufour, Xavier; Malard, Olivier; Pretet, Jean-Luc; Clavel, Christine; Birembaut, Philippe; Franceschi, Silvia; et al.
Highlights: 27% oropharyngeal cancer patients (France) were HPV+; many were also smokers. HPV+ patients had 2-fold better progression-free survival (PFS) than HPV-negative. Only lack of upfront surgery had an equally strong effect on PFS as HPV. Lack of upfront surgery was especially detrimental in HPV-negative patients. Poorer PFS in HPV-negative may derive from more genomic damage or bulkier tumours. Abstract: Aims: To evaluate the impact of human papillomavirus (HPV) status, tobacco smoking and initial treatment approach on progression-free survival (PFS) and overall survival (OS) for oropharyngeal cancer (OPC) in France, a country where smoking declines started late (1990s). Methods: 340 OPC patients (median age: 60 years) from 14 French hospitals were followed up (median 26.7 months). PCR-based positivity for both HPV DNA and E6/E7 mRNA was used to distinguish HPV-positive OPC (27.1%). Hospital-stratified hazard ratios (HR) and corresponding 95% confidence intervals (CI) were used to compare PFS and OS according to HPV and other prognostic factors in hospital-stratified unadjusted and multivariate models. The combined effect of HPV status with either smoking, stage, or initial treatment on PFS was also evaluated. Results: PFS in multivariate analysis was better in HPV-positive patients (HR = 0.42; 95% CI: 0.24–0.73) and worse in older patients (HR for 5-year age increase = 1.12) and those having had firstly radiotherapy (HR = 1.86; 95% CI: 1.19–2.92) or induction chemotherapy (HR = 1.73; 95% CI: 1.08–2.79) instead of upfront surgery. Findings for OS were similar. Loco-regional recurrences were less frequent in HPV-positive (10.5%) than HPV-negative patients (26.0%) but distant recurrences were similarly frequent. HPV status did not modify the influence of smoking or stage on PFS but the impossibility to perform upfront surgery may be more relevant for HPV-negative patients. Conclusions: HPV-positive OPC patients fare better than HPV-negative OPC and may benefit from toxicity-sparing. Whether HPV-negative patients responded less well to radiation and chemotherapy because of more severe genomic damage or bulkier tumours is unclear.